2019
DOI: 10.3390/ijms20051218
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2-Mediated Up-Regulation of Mitochondrial Transcription Factor A Mitigates the Radio-Sensitivity of Cancer Cells

Abstract: Mitochondrial transcription factor A (TFAM) regulates mitochondrial biogenesis, and it is a candidate target for sensitizing tumor during therapy. Previous studies identified that increased TFAM expression conferred tumor cells resistance to ionizing radiation. However, the mechanisms on how TFAM are regulated in irradiated tumor cells remain to be explored. In this research, we demonstrated the contribution of cyclooxygenase-2 (COX-2) to enhancing TFAM expression in irradiated tumor cells. Our results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…In the current study, COX-2-knockdown based on CRISPR/Cas9 suppressed mito-COX-2/p-Drp1 Ser616 interaction and increased the chemosensitivity of HCC. Consistent with our results, Tang et al found that inhibition of COX-2 by NS-398 sensitized cancer cells to radiotherapy via the downregulation of the p38/Drp1/TFAM signaling axis, mediating mitochondrial fission [49]. Suppression of Drp1-driven mitochondrial fission enhanced the sensitivity of hypoxic ovarian cancer cells to cDDP [61].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, COX-2-knockdown based on CRISPR/Cas9 suppressed mito-COX-2/p-Drp1 Ser616 interaction and increased the chemosensitivity of HCC. Consistent with our results, Tang et al found that inhibition of COX-2 by NS-398 sensitized cancer cells to radiotherapy via the downregulation of the p38/Drp1/TFAM signaling axis, mediating mitochondrial fission [49]. Suppression of Drp1-driven mitochondrial fission enhanced the sensitivity of hypoxic ovarian cancer cells to cDDP [61].…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that the multi-kinase framework including ERK/AKT and CDK2 promotes cell proliferation of A549 and HCC827 cells by activating Drp1 [48]. Tang et al [49] found that COX-2 contributed to the upregulation of mitochondrial transcription factor A (TFAM), mediated by p38-MAPK activation, and the subsequent enhancement of Drp1-dependent mitochondrial fission in human osteosarcoma U-2 OS and cervical cancer HeLa cells. However, the mechanisms remain to be elucidated for how p-Drp1 Ser616 is regulated in HCC cells with high COX-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the functions of TEFM in HCC, another mitochondrial transcription regulator TFAM also has been reported to induce G1 cell cycle transition, but inhibit cell apoptosis in glioma and non-small cell lung cancers 17 , 20 . Besides the tumor growth promoting role, increased TFAM also confers resistance to ionizing radiation in several types of malignances 17 , 21 , 22 , further supporting an inhibitory role for TFAM in tumor cell apoptosis. Meanwhile, we also tested the effect of TEFM on metastasis of HCC and found that TEFM knockdown decreased the migration and invasion of SNU-354 and SNU-739 cells, while TEFM over-expression enhanced the migration and invasion of HUH-7 and HLF cells.…”
Section: Discussionmentioning
confidence: 86%
“…The activities of phospholipase A2, COX and PGE 2 synthases are essential to the biosynthesis of PGE 2 . A previous study demonstrated that COX-2 is rapidly induced by oncogenes, growth factors, cytokines and tumor promoters, and serves an important role in the development of cancer (34). Furthermore, COX-2 regulates tumor growth by binding to its corresponding receptors through various downstream prostate products, instead of acting as a signal transduction kinase.…”
Section: Discussionmentioning
confidence: 99%